Performance in adults of the EULAR/PRINTO/PRES (Ankara 2008) classification criteria for IgA vasculitis - Ömer Karadağ; Seza Ozen; Cristina Ponte; Richard A Watts; Raashid Ahmed Luqmani; Peter C Grayson; Peter A Merkel; Ravi Suppiah; Joanna C Robson; Alexandra Audemard-Verger; Selcan Demir; Cemal Bes; et al. (RMD Open)
Objective To examine the performance in adults of the European Alliance of Associations for Rheumatology (EULAR)/Pediatric Rheumatology European Society (PReS)-endorsed Ankara 2008 classification criteria for IgA vasculitis (IgAV).Methods The EULAR/PReS/Ankara 2008 classification criteria for IgAV were applied to patients enrolled in an international observational cohort which included patients with IgAV and comparators with other forms of small-vessel and medium-vessel vasculitis. After the initial assessment of the performance of the criteria, possible revisions to increase the performance were tested. The revised criteria were then assessed in an independent validation cohort within a multicentre Turkish vasculitis registry.Results The dataset consisted of 178 IgAV cases and 1705 comparators. The Ankara 2008 criteria require skin involvement plus one of the following four criteria: abdominal pain, a biopsy showing IgA deposition, arthritis or arthralgia, or renal involvement (any haematuria and/or proteinuria). The specificity of the criteria improved when a positive test for anti-neutrophil cytoplasmic autoantibody or blood cryoglobulins was considered an exclusion criterion. The revised criteria had a sensitivity of 76.4% (95% CI 69.8% to 82.2%) and a specificity of 94.5% (95.0% CI 93.4% to 95.1%). In the validation set, the sensitivity and specificity of the revised criteria were 97.8% (95% CI 94.0% to 99.0%) and 85.0% (95.0% CI 78.0% to 90.0%), respectively.Conclusion The revised EULAR/PReS-endorsed Ankara 2008 IgAV classification criteria perform well in adults with IgAV and are appropriate for use in clinical research.